MO126CLINICAL AND BIOMARKER CHARACTERISTICS OF PATIENTS WITH C3G OR IC-MPGN ENROLLED IN TWO PHASE II STUDIES INVESTIGATING THE FACTOR D INHIBITOR DANICOPAN*. (29th May 2021) - Nester, Carla; Podos, Steven; Hogan, Jonathan; Appel, Gerald; Bomback, Andrew; Bouman, Koen; Cook, Terry; Daina, Erica; Dixon, Bradley; Langman, Craig; Lightstone, Liz; Thanassi, Jane; et al.
Abstract: Background and Aims: C3 glomerulopathy (C3G) and immune complex membranoproliferative glomerulonephritis (IC-MPGN) are rare, progressive kidney diseases requiring a biopsy for definite diagnosis. Both C3G and IC-MPGN are attributed to complement dysregulation, with dysregulation of the alternative pathway established in C3G and implicated in IC-MPGN (alongside classical pathway activation by immune complexes). We describe the baseline biomarker and clinical characteristics of patients participating in two C3G/IC-MPGN phase II studies of the investigational, oral complement factor D (FD) inhibitor, danicopan (ALXN2040/ACH-4471). Method: The first study (NCT03369236) was a double-blind, placebo-controlled, randomised, 6-month (+open label extension) trial of patients with biopsy-confirmed C3G of the native kidney treated with danicopan or placebo. The second study (NCT03459443) was a single-arm, open-label, 12-month (+extension) trial of patients with biopsy-confirmed C3G or IC-MPGN treated with danicopan. In both studies, all patients were to have proteinuria ≥500 mg/day and estimated glomerular filtration rate (eGFR) ≥30 mL/min/1.73 m 2 (calculated by the Modification of Diet in Renal Disease equation for patients ≥18 years and the Schwartz equation for patients <18 years). Complement biomarkers including, but not limited to, C3, C4, AP activity, classical pathway activity, FD, Ba, Bb, sC5b-9, and C5 were measured in serum or plasma prior to dosing. Spearman correlation coefficients (rs ) were determined between biomarkers of complement, eGFR, and/or proteinuria. Results: A total of 35 patients were included in this analysis (13 from study 1 and 22 from study 2). The majority of patients were male (9 [69%] in study 1, 12 [55%] in study 2), with mean (SD) ages at baseline of 25.2 (7.63) years in study 1 and 24.3 (9.90) years in study 2. Most patients had received prior angiotensin converting enzyme inhibitors/receptor blockers (12 [92%] in study 1, 19 [86%] in study 2), and/or immunosuppressants (10 [77%] in study 1, 12 [55%] in study 2). Baseline clinical and biomarker data are shown in Table 1. Baseline eGFR was moderately correlated with proteinuria (uPCR24, rs =-0.40 [p=0.022]); baseline uPCR24 was also moderately correlated with Ba (rs =0.42 [p=0.016]) and FD (rs =0.53 [p=0.002]). Ba and FD elevations showed strong correlations with lower eGFR (rs =-0.79 and -0.88, respectively [p<0.0001]), as seen in Figure 1A and B. Reduced circulating C3 strongly correlated with increased sC5b-9 (rs =-0.70 [p<0.0001]) and reduced C5 level (rs =0.80 [p<0.0001]), as seen in Figure 1C and D . Conclusion: Data from two danicopan clinical studies in C3G patients show correlations with renal impairment and proteinuria were observed for some, but not all, complement biomarkers. Factor Ba and FD are strongly associated with eGFR, suggesting that these biomarkers cannot easily be used as markers of complement dysregulation or activity. Interpretation of changes in these complement proteins needs to include not only the nature of the complement dysregulation and influence of the complement therapeutic being tested, but also eGFR. Additional urinary biomarkers, biopsy findings, autoantibodies, and genetic variants are currently being analysed and findings from this study will contribute to a better understanding of C3G and IC-MPGN.